Factors Determining the Susceptibility of Bacteria to Antibacterial Photodynamic Inactivation - Rapacka-Zdończyk, Aleksandra; Woźniak, Agata; Michalska, Klaudia; Pierański, Michał; Ogonowska, Patrycja; Grinholc, Mariusz; Nakonieczna, Joanna (Frontiers in Medicine, 2021)
Photodynamic inactivation of microorganisms (aPDI) is an excellent method to destroy antibiotic-resistant microbial isolates. The use of an exogenous photosensitizer or irradiation of microbial cells already equipped with endogenous photosensitizers makes aPDI a convenient tool for treating the infections whenever technical light delivery is possible. Currently, aPDI research carried out on a vast repertoire of depending on the photosensitizer used, the target microorganism, and the light delivery system shows efficacy mostly on in vitro models. The search for mechanisms underlying different responses to photodynamic inactivation of microorganisms is an essential issue in aPDI because one niche (e.g., infection site in a human body) may have bacterial subpopulations that will exhibit different susceptibility. Rapidly growing bacteria are probably more susceptible to aPDI than persister cells. Some subpopulations can produce more antioxidant enzymes or have better performance due to efficient efflux pumps. The ultimate goal was and still is to identify and characterize molecular features that drive the efficacy of antimicrobial photodynamic inactivation. To this end, we examined several genetic and biochemical characteristics, including the presence of individual genetic elements, protein activity, cell membrane content and its physical properties, the localization of the photosensitizer, with the result that some of them are important and others do not appear to play a crucial role in the process of aPDI. In the review, we would like to provide an overview of the factors studied so far in our group and others that contributed to the aPDI process at the cellular level. We want to challenge the question, is there a general pattern of molecular characterization of aPDI effectiveness? Or is it more likely that a photosensitizer-specific pattern of molecular characteristics of aPDI efficacy will occur?